Effects of Intravenous Test Dose Epinephrine on Fetal Sheep during Acute Fetal Stress and Acidosis. Issue 5 (September 1990) - Youngstrom, Paul; Cohen, Ilan; Hoyt, Mccallum; Amini, Saeid; Veille, J. C.; Herman, Michael
Abstract : Small IV doses of epinephrine (epi; 5.0-20.0 μg), similar to those advocated for epidural test dosing, cause a significant though transient (3 minutes) reduction in uterine blood flow in pregnant ewes but no subsequent adverse effect on the mature, unstressed fetus. The purpose of this study was to investigate the acute effects on the mature fetus of a maternal IV test dose of 12.5 mg bupivacaine and 50.0 μg fentanyl with or without 16.5 μg epi in the presence of acute placental insufficiency and fetal asphyxia. Two minutes after dosing and for 15 minutes thereafter, no changes were observed in maternal heart rate (HR), mean arterial pressure (MAP) or arterial blood gas values and catecholamine concentrations other than a statistically significant doubling in epi levels after epi dosing. Mildly (mean arterial pH, 7.23) and severely (mean pH, 6.87) acidotic fetuses differed with respect to arterial pO2, pCO2 and catecholamine values, but in neither group were any changes observed after maternal dosing. Under the conditions of acute fetal stress and acidosis produced in this experiment, inclusion of epi 16.5 μg in an epidural test dose does not significantly affect the HR, MAP, aortic flow, blood gases or catecholamine levels of the mature fetal sheep when injected intravenously.